Relações entre saúde e trabalho na perspectiva de trabalhadores de um centro de convivência e cultura - Arduini, Glendha Oliveira (2022)
Work is a constituent element of the professionals' identity and subjectivity and has been associated with overload and psychic suffering. Workers in mental health institutions are exposed to intrinsic psychosocial risks and those arising from the work organization, intensified by the historical-sanitary moment of pandemic caused by Covid-19 virus. The objective was to analyze how the workers of a Center of Coexistence and Culture (CECO) understand their performance in the field of mental health and the relations between their work and health. This is a descriptive study with a qualitative methodological approach developed with eleven workers from a CECO in the interior of state of Minas Gerais. In the construction of data, were used a semi-structured interview and a socio-demographic characterization form. With the thematic content analysis of the interviews, three categories were outlined: CECO dynamics; Worker's Mental Health; Outsourcing. Most participants are female. Age varied 31 to 61 years, and 90.9% of the workers were adults and one was elderly; were in a union (54.5%), had a higher education degree (81.8%) and of these, 54.5% had completed graduate studies. The time working in the area of health and mental health varied 8 to 32 years, with a predominance of workers with experience of 21 years and more (45.4%). Regarding the performance in CECO, there was a variation from three to 12 years, with predominant (54.5%) from 1 to 10 years. The celetista labor bond involved 54.5% of the participants. The majority (81.8%) worked exclusively in CECO. The weekly workload at the institution varied from 20 to 40 hours, with 30 hours being predominant (54.5%). The Ceco Dynamics category refers to the institution's fundamental role in the rehabilitation process of users. The participants detailed the activities developed, the specificities of the care offered and the relationships with the health care network and other partner institutions. The Worker's Mental Health category includes factors that contribute to professional satisfaction, such as recognition by users and qualification, and situations that cause suffering, change of the outsourced company responsible for managing and changes in institutional dynamics in the Covid-19 pandemic. Outsourcing was treated by the participants as a setback in the field of mental health, rupture of association partnerships and reduction of workers' autonomy, generating helplessness and demotivation due to a verticalized and bureaucratized work organization. This study showed that workers consider CECO as an essential care device for the field of mental health, although they face uncertainties for its maintenance. The Covid-19 pandemic exacerbated the challenges for maintaining the service and strengthened aspects of the organization of work by the outsourced company considered by workers as generators of dissatisfaction with work, psychic suffering and occupational illness.